Mechanical and physical properties of bottom ash/fly ash geopolymer for pavement brick application. Issue 1 (February 2020) - Wan Ibrahim, Wan Mastura; Bakri Abdullah, Mohd Mustafa Al; Ahmad, Romisuhani; Mohd Tahir, Muhammad Faheem; Mohd Mortar, Nurul Aida; Noor Azli, Muhammad Amirul Aziem
Abstract: Geopolymers are amorphous to semi-crystalline with excellent physical and and mechanical properties. It has been used to become a potential binder to Ordinary Portland Cement (OPC) in certain applications due to its lower emission of carbon dioxide gases and low energy consumption sustainability criteria. Bottom Ash (BA) is one of the main industrial by-products and it is produced at the bottom of the furnace during the coal combustion process in electricity generation. The application of BA as a sustainable construction material in the building industry plays an important role in order to decrease the volume of residual waste and conserving existing natural fine aggregates. The objectives for this study is to study the effect of fly ash to bottom ash ratio and to determine the optimum ratio of fly ash to bottom ash geopolymer for pavement brick application. The chemical composition and morphology of geopolymer reinforcement was analysed by using X-ray Fluorescence and Scanning Electron Microscope. The molarity of the Sodium Hydroxide solution is fixed at 12M. The parameter used in this study are different weight percentage of fly ash geopolymer 0 wt%, 10 wt%, 20 wt%, 30 wt% and 40 wt%. The solid to liquid ratios for this study is 2.0. The curing temperature of this study is 80°C and the curing time is 24 hours. 100% of bottom ash geopolymer is used as a control variable for this study.